2017
DOI: 10.1002/ajhb.23066
|View full text |Cite
|
Sign up to set email alerts
|

Resting metabolic rate of Indian Junior Soccer players: Testing agreement between measured versus selected predictive equations

Abstract: FFM explained variation in RMR across age and sex. The FFM-based Soares et al. (, British Journal of Nutrition, 79) equation for girls and body weight-based Wong et al. (, Singapore Medical Journal, 53) equation for boys are best suited for predicting RMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 15 publications
2
8
1
Order By: Relevance
“…In accordance with changes in stature, body mass and FFM, we also observed an increase in RMR between the U12-U14 age groups (U12: 1655 ± 195 kcal.day -1 ; U13 1720 ± 205 kcal.day -1 ; U14: 1846 ± 218 kcal.day -1 ), thus highlighting the requirement to adjust total energy intake accordingly. Such data correspond with data from Indian soccer players where an increase in RMR of ~400 kcal.day -1 from the ages of 10 to 13 (Cherian et al, 2018) was also observed. It is noteworthy, however, that the RMR values in the present study are higher than those previously reported in youth soccer players.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In accordance with changes in stature, body mass and FFM, we also observed an increase in RMR between the U12-U14 age groups (U12: 1655 ± 195 kcal.day -1 ; U13 1720 ± 205 kcal.day -1 ; U14: 1846 ± 218 kcal.day -1 ), thus highlighting the requirement to adjust total energy intake accordingly. Such data correspond with data from Indian soccer players where an increase in RMR of ~400 kcal.day -1 from the ages of 10 to 13 (Cherian et al, 2018) was also observed. It is noteworthy, however, that the RMR values in the present study are higher than those previously reported in youth soccer players.…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, an assessment of RMR (a major component of total energy expenditure; TEE) at least provides a platform to begin to develop age-specific energy requirements. Indeed, data from Indian youth soccer players demonstrates that RMR increases by ~400 kcal.day -1 from the (chronological) ages of to 13 (Cherian et al, 2018). To the authors' knowledge, however, no research has yet quantified RMR in Premier League academy soccer players across the full age-range of a professional soccer academy, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The differences in the value of the REE between the children from the circum and post groups were not statistically significant (p = 0.2804). These results are in agreement with the data of a previous study on Indian soccer players, where an increase in REE of about 400 kcal/day from the ages of 10 to 13 was also noticed [31]. A similar effect was observed by Hannon et al, who also showed an increase in REE between the U12 and U14 (Football Academy Categories) age groups [32].…”
Section: Discussionsupporting
confidence: 93%
“…However, the IC technique is time-consuming, expensive, and, unavailable in daily practice. Accordingly, REE as well as TEE are often predicted via one of various prediction equations (Vander Weg et al, 2004;ten Haaf and Weijs, 2014;Cherian et al, 2018;Amaro-Gahete et al, 2019;Schofield et al, 2019). The Harris & Benedict (H&B), World Health Organization (WHO), Müller (MÜL), Müller-FFM (MÜL-FFM) and Cunningham (CUN) equations are most commonly used, but none of these standard prediction equations fits for every individual.…”
Section: Introductionmentioning
confidence: 99%